Physical properties of self-polarized PZT thin films at compositions around the morphotropic phase boundary - Araújo, Eudes Borges de [UNESP]; Lima, Elton Carvalho de; Bdikin, Igor K.; Kholkin, Andrei L. (Trans Tech Publications Ltd, 2014)
The physical properties of self-polarized PbZr1-xTixO3 thin films with no preferential orientation in a range of compositions 0.46 <= x <= 0.50 were investigated. Structural analysis revealed the coexistence of monoclinic-tetragonal and monoclinic-rhombohedral phases at compositions 0.46 <= x <= 0.49, where the monoclinic phase was in the majority and both the tetragonal and the rhombohedral phases in the minority. The dielectric permittivity (epsilon'= 447) reached its maximum at around composition x = 0.48. Asymmetries in the macroscopic and local hysteresis loops confirmed the existence of the self-polarization effect in the studied films.
Keywords: PZT films; Self-polarization; Piezoelectric